The Artist's Handbook of Materials and Techniques - Mayer, Ralph (Faber and Faber, 1973)
The Artist's Handbook has become an indispensable reference work for thousands of practising artists all over the world. This fifth edition has been prepared by Steven Sheehan, Director of the Ralph Mayer Center, Yale University School of Art. It has been systematically revised and expanded to take account of the latest research. Once again, it has been edited for the British market.The Artist said of the previous major revision:'.In the first place the third edition of The Artist's Handbook has been so extensively revised that it might well be classified as a new book; and secondly, it is of major importance in the field of art .there is no other book which is as extensive in its coverage nor any one which enjoys quite the reputation that has accrued to this'. -- cover. Pigments - Oil paintings - Acrylics - Tempera painting - Oil and tempera - Watercolour and gouache - Pastel - Encaustic painting - Mural painting - Solvents and thinners - Gums, casein, glues, waxes - Chemistry - Conservation of pictures.